Alih Kode dan Campur Kode dalam Pembelajaran Bahasa Indonesia - Hizbi Naufal Azis; Laili Etika Rahmawati (Institut Agama Islam Negeri Curup, 2021)
This study aims to describe the form of code switching and code mixing used in Indonesian language learning at SMP N 01 Limpung, Batang Regency. This research is included in qualitative descriptive. Data processing that examines code switching and code mixing is thus the data in this study in the form of oral data, namely, speech code switching and code mixing that exist in Indonesian language learning. The data sources came from Indonesian language students and teachers at SMP N 01 Limpung. Data collection techniques in this study used the observation and note technique. The first step, the researcher listens to the use of language in Indonesian language learning. Furthermore, the researcher recorded the speech data including code switching and code mixing. The results showed that the speech used when learning Indonesian at SMP N 01 Limpung included: (1) code switching from Indonesian to Javanese and (2) code switching from Javanese to Indonesian. The form of code mixing that occurs in Indonesian language learning is in the form of: (1) the form of code mixing in the form of word insertion, (2) code mixing in the form of phrases